GENERAL THEORETICAL SETTINGS ON THE PRINCIPLE OF IMMEDIACY IN CRIMINAL PROCEEDINGS - Brkić, Snežana S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
The paper presents some general theoretical settings about the principle of immediacy in criminal proceedings. It should serve as a theoretical platform for developing further research in this area. The autor gives a definition of the principle of immediacy and sees his place in the classification of procedural principles, linking it to the judicial function. The principle of immediacy is one of the implicit procedural principles, which also have international legal roots in Art. 6 of the European Convention for the Protection of Human Rights and fundamental freedoms. The paper emphasizes and analyzes the following important features of the principle of immediacy: instrumentality, complexity, relativity (susceptibility to gradation) and connection with other procedural principles.